Effects of municipal sludge and treated waste water on biomass yield and fiber properties of kenaf (Hibiscus cannabinus L.) - Ververis, C.; Christodoulakis, N.S.; Santas, R.; Santas, P.; Georghiou, K. (Industrial Crops and Products, 2016)
Kenaf (Hibiscus cannabinus L.) was experimentally cultivated with the use of digested, dried sewage sludge (130 t/ha) and water from a municipal Sewage Treatment Plant (STP) in order to assess their potential to replace conventional fertilization (100 kg N/ha, 75 kg P2O5/ha and 75 kg Κ2O/ha) and irrigation. Tap water and treated wastewater were used for irrigation in quantities corresponding to 6500 m3/ha. Four different treatment combinations were applied as follows: (a) wastewater irrigation and conventional fertilization, (b) wastewater irrigation and sewage sludge fertilization, (c) tap water irrigation and sewage sludge fertilization, and (d) tap water irrigation and conventional fertilization. The dry plant biomass collected in the final harvest (140 days after plant emergence) from the four treatment plots was 12.3 t/ha, 12.6 t/ha, 12.4 t/ha and 12.8 t/ha respectively. These differences were not statistically significant (ANOVA, P = 0.05) and, therefore, it was concluded that the use of municipal wastes had similar effects on dry biomass production with that of conventional fertilization. An earlier harvest (125 days after plant emergence) gave 11.3% lower dry biomass on average in relation to the second harvest, and this difference was statistically significant (ANOVA, P = 0.05). Premature harvest may lead to significant biomass losses, so the plant must be collected during its technological maturity stage. There was not any statistically significant difference among the four treatments and between the two harvests in fiber dimensions and derived values (suitability indices for paper manufacture). On the other hand, cellulose and lignin content in the second harvest were significantly higher compared to the first one, whereas no significant differences were detected among the four treatments. © 2016 Elsevier B.V.
Keywords: Analysis of variance (ANOVA); Biomass; Different treatments; Fiber properties; Harvesting; Hemp; Hibiscus cannabinus; Irrigation; Kenaf; Kenaf (Hibiscus cannabinus L.); Municipal sewage treatment plant; Municipal waste; Sewage sludge; Sewage treatment plants; Statistically significant difference; Wastewater irrigation; Wastewater treatment; Water treatment